Monitoring Battery Charging Using Node-RED - Nur Vidia Laksmi B.; Muhammad Syahril Mubarok; Reza Rahmadian; Mahendra Widyartono; Ayusta Lukita Wardani; Aditya Chandra Hermawan; Muhammad Abdus Salam (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
The need for a smart grid has been spurred by the growth of distributed generation, the aging of the current grid infrastructure, and the desire to alter networks. The development and enhancement of smart grid technology is significantly facilitated by the Internet of Things (IoT) technology. Batteries play a crucial role in the energy storage of electrical systems, including smart microgrids and electric vehicles. To enhance performance and prolong battery life, a Battery Monitoring System (BMS) is required to manage the energy storage process dynamics within the battery. Battery life prediction contributes to the consistent and efficient operation of battery-powered devices. This research presents battery charging monitoring using Nodered. Apart from that, the battery charging feature uses a cut-off concept. The cut off on the battery is to prevent the battery from over-discharging which can damage the battery and shorten its lifespan. This research carried out validation using 3 case studies on battery charging. Validation of measurements uses a comparison between the INA 219 sensor and a multimeter. From experiments, current testing from 3 case studies, it was found that the average difference in current sensor error was 0.19%.